2015
DOI: 10.1186/s40880-015-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Elevated peripheral blood lymphocyte-to-monocyte ratio predicts a favorable prognosis in the patients with metastatic nasopharyngeal carcinoma

Abstract: IntroductionPatients with metastatic nasopharyngeal carcinoma (NPC) have variable survival outcomes. We have previously shown that an elevated peripheral blood lymphocyte-to-monocyte ratio (LMR) is associated with an increased metastatic risk in patients with primary NPC. The present study aimed to investigate the prognostic value of pretreatment LMR in a large cohort of metastatic NPC patients.MethodsClinical data of 672 patients with metastatic NPC diagnosed between January 2003 and December 2009 were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 37 publications
1
53
0
Order By: Relevance
“…The association between LMR and OS was reported in 44 studies enrolling 14,984 patients with various cancer types [8, 1013, 1517, 1921, 2327, 2933, 3540, 4246, 48, 49, 51, 53–56, 5862]. Five of the eligible 44 studies (11%) reported a non-statistically significant hazard ratio.…”
Section: Resultsmentioning
confidence: 98%
“…The association between LMR and OS was reported in 44 studies enrolling 14,984 patients with various cancer types [8, 1013, 1517, 1921, 2327, 2933, 3540, 4246, 48, 49, 51, 53–56, 5862]. Five of the eligible 44 studies (11%) reported a non-statistically significant hazard ratio.…”
Section: Resultsmentioning
confidence: 98%
“…The sample sizes of the included studies ranged from 62 to 1895, and a total of 11,651 cases were included. Four studies focused on metastatic NPC, [21,22,23,27] whereas 10 studies only included patients with nonmetastatic NPC. [1620,2426,28,29] The majority of studies assessed the patients’ hematologic parameters before treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The NOS scores of the included studies were around 6 to 7, and the most common inadequacies in methodology were the use of a retrospective study design and incomparability between groups. The cut-off values of hematologic parameters, including NLR, PLR, LMR, lymphocyte counts, and monocyte counts,were determined by receiver-operating characteristic curves to select the most significant points in most studies; [16,18,20,23,25,27,29] Apart from this, the study conducted by He et al [17] and Jiang et al [28] chose quartilevalues as cut-off points artificially. Because the cut-off value of hematologic parameters was artificially chosen to acquire the most significant effect and the clinicopathological features between groups in each study were incomparable, there could be both inter and intrastudy variability; thus, it was reasonable to use a random-effects model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systemic inflammatory markers, particular clinically accessible ones, have been studied as prognostic and predictive factors, and have been incorporated into prognosis scores for several types of cancer. These include C-reactive protein (CRP) [14,15,16], the neutrophil/lymphocyte ratio (NLR) [17,18], the Glasgow Prognostic Score (GPS) [19,20], the platelet/lymphocyte ratio [21], the absolute lymphocyte count [22], and the lymphocyte/monocyte ratio [23]. The assessment of inflammatory response to a tumor using these laboratory markers is relatively straightforward and cost-effective in clinical practice.…”
Section: Introductionmentioning
confidence: 99%